Great writing 2 : - Folse, Keith S. (Heinle, Cengage Learning, 2010)
Clear Explanations And Extensive Practical Activites Help Students Write Great Sentences, Paragraphs And Essays. Each Book Contains A Wide Variety Of Writing Models In Carefully Selected Rhetorical Styles That Provide Practice In Working With The Writing Process To Develop A Final Piece Of Writing.